Determinan Pengungkapan Pajak di Indonesia (Determinants of Tax Disclosure in Indonesia) - Wardoyo, Eirene Puspita; Sari, Dian Purnama (STIE Malangkucecwara, 2023)
Tax disclosure has become a debate, namely whether the existence of tax disclosure can increase tax compliance. Dangerous tax practices such as illegal tax planning by companies create public pressure to prevent and end such acts. This pressure is overcome by increasing compliance and accountability through increasing taxpayer disclosure of information that can be accessed by the public. This study aims to analyze and examine the effect of tax planning, utilization of tax havens, and managerial ownership on corporate tax disclosure. The research object used is a manufacturing company listed on the Indonesia Stock